The Functions of Regional Business Organizations: A Survey of Taiwanese IT Firms in Europe - Su, Julie (Marketing & Menedzsment, 2019)
The aim of this study is to examine the strategic move of Information Technology (IT) original equipment manufacturers (OEMs) in a region. As the IT firms are increasingly regionally based, this paper examines the functions of regional organizations of newly developed IT firms from Taiwan. By adopting a qualitative method with case survey on selected cases - Taiwan’s Acer and Foxconn - in Europe, it is found that their regional organizations were continually shaped in order to efficiently perform their independent decision-making and coordination-integration functions. These main functions could be regarded as two dimensions applied to categorize regional organizations into a functional matrix.